Manajemen Pengembangan Bakat Dan Minat Pada Peserta Didik Sekolah Menengah Atas Islam Terpadu Al-Fityan School Gowa - Muh Nasir B; Rusli Malli (Universitas Muslim Indonesia, 2022)
This study aims to identify and analyze: 1. planning for the development of interests and talents of SMAIT Al Fityan School students 2. implementing the development of interests and talents of students at SMAIT Al Fityan School Gowa. 3. evaluate the development of interests and talents of SMAIT Al Fityan School Gowa students SMAIT Al fityan School Gowa has management that manages the development of students' interests and talents and specifically channels the talents and interests of students with separate programs and is carried out systematically, so as to achieve maximum results. This research is descriptive qualitative, which is a research that is intended to reveal an empirical fact scientifically objectively based on scientific logic, and procedures and supported by a strong methodology and theory according to the scientific discipline being occupied. The results of the study indicate that the management of talent and interest development in students at SMAIT Al-fityan school gowa is quite effective in shaping the character of creative behavior, leadership behavior, academic behavior and increasing students' academic talent and potential and as participants who will be sent by the party. schools in various competitions.